Sir Benjamin Collins Brodie (1783–1862) – a pioneer rheumatologist. (June 2015) - Travers, Richard; Sayag‐Boukris, Véronique
Abstract Aim Sir Benjamin Collins Brodie (1783–1862) was a London surgeon who investigated joint disease by observation and morbid anatomy in the first half of the 19th century. His descriptions of inflammatory joint disease have been referred to in the past, but only in a fragmentary way. This study aimed to provide more detail than previously, allowing for a new appreciation of his contributions. Methods The authors used the first (1818), third (1834) and fifth (1850) editions of his book, Pathological and Surgical Observations on the Diseases of Joints, to provide his description of reactive arthritis, rheumatoid arthritis and ankylosing spondylitis. Results Brodie's descriptions are admirably clear. He describes reactive arthritis in the first edition of his book more completely than authors before him and even Reiter a century later. He recognised that the conjunctivo‐urethral‐synovial syndrome can occur independently of gonorrhoea, that there are often repeated attacks, and that irits is a complication – the first indication that this syndrome might be part of what we now call seronegative spondyloarthritis. The fifth edition (1850) has among the earliest descriptions in English of ankylosing spondylitis and rheumatoid arthritis. Conclusion Brodie's understanding of rheumatic diseases, and his willingness to pass this knowledge on, demands that he be widely recognised as a pioneer rheumatologist.